Trypanocidal activity of mastoparan from Polybia paulista wasp venom by interaction with TcGAPDH. (October 2017) - Vinhote, Juliana Freire Chagas; Lima, Dânya Bandeira; Menezes, Ramon Róseo Paula Pessoa Bezerra de; Mello, Clarissa Perdigão; de Souza, Bibiana Monson; Havt, Alexandre; Palma, Mario Sérgio; Santos, Ricardo Pires dos; Albuquerque, Eudenilson Lins de; Freire, Valder Nogueira; Martins, Alice Maria Costa
Abstract: Chagas disease, considered a neglected disease, is a parasitic infection caused by Trypanosoma cruzi, which is endemic throughout the world. Previously, the antimicrobial effect of Mastoparan (MP) from Polybia paulista wasp venom against bacteria was described. To continue the study, we report in this short communication the antimicrobial effect of MP against Trypanosoma cruzi . MP inhibits all T. cruzi developmental forms through the inhibition of Tc GAPDH suggested by the molecular docking. In conclusion, we suggest there is an antimicrobial effect also on T. cruzi . Highlights: Mastoparan from Polybia paulista wasp venom (MP) possess trypanocidal effect. MP was effective over all main forms of Trypanosoma cruzi . MP causes induction of cytoplasmic ROS and mitochondrial dysfunction. MP could interact with Tc GAPDH.